Ordem de Serviço PRR4 nº 16, de 3 de dezembro de 2021 - Antonio Carlos Welter (DMPF-e, Brasília, DF, 7 dez. 2021. Caderno Administrativo, p. 42., 2021)
Determina a alocação das servidoras: MARIANA ONOFRIO ROCHA, MARIA ROSA AVINO, FERNANDA GRASSELLI RAMPON, NORIS LIMA KERN, VANIA MARTINEZ e SONIA FERREIRA CARDOZO .